Determinants of Purchasing Selected FMCG Products in India: Evidence from Agartala City - Dey, Trinankur; Sharma, L. S. (Indian Journal of Marketing, 2019)
The paper examined the factors of decision making while purchasing selected FMCG products in India. Data were collected from 256 FMCG consumers of Agartala city by using a structured questionnaire developed based on the earlier studies. Kendall's W was predominantly used to analyze the data. The study found that for most of the selected categories of FMCG products, the main decision making was based on availability of the products followed by freshness for non-packaged products (expiry, latest products, etc. for packaged products). Demographic factors were also found to be playing a dominant role in the purchase decisions of FMCG products.